Left DLPFC activity is associated with plasma kynurenine levels and can predict treatment response to escitalopram in major depressive disorder. Issue 8 (1st June 2022) - Kamishikiryo, Toshiharu; Okada, Go; Itai, Eri; Masuda, Yoshikazu; Yokoyama, Satoshi; Takamura, Masahiro; Fuchikami, Manabu; Yoshino, Atsuo; Mawatari, Kazuaki; Numata, Shusuke; Takahashi, Akira; Ohmori, Tetsuro; et al.
Abstract : Aim: To establish treatment response biomarkers that reflect the pathophysiology of depression, it is important to use an integrated set of features. This study aimed to determine the relationship between regional brain activity at rest and blood metabolites related to treatment response to escitalopram to identify the characteristics of depression that respond to treatment. Methods: Blood metabolite levels and resting‐state brain activity were measured in patients with moderate to severe depression ( n = 65) before and after 6–8 weeks of treatment with escitalopram, and these were compared between Responders and Nonresponders to treatment. We then examined the relationship between blood metabolites and brain activity related to treatment responsiveness in patients and healthy controls ( n = 36). Results: Thirty‐two patients (49.2%) showed a clinical response (>50% reduction in the Hamilton Rating Scale for Depression score) and were classified as Responders, and the remaining 33 patients were classified as Nonresponders. The pretreatment fractional amplitude of low‐frequency fluctuation (fALFF) value of the left dorsolateral prefrontal cortex (DLPFC) and plasma kynurenine levels were lower in Responders, and the rate of increase of both after treatment was correlated with an improvement in symptoms. Moreover, the fALFF value of the left DLPFC was significantly correlated with plasma kynurenine levels in pretreatment patients with depression and healthy controls. Conclusion: Decreased resting‐state regional activity of the left DLPFC and decreased plasma kynurenine levels may predict treatment response to escitalopram, suggesting that it may be involved in the pathophysiology of major depressive disorder in response to escitalopram treatment.